Anticipatory Governance in Developing Countries Toward a Bottom-Up Approach in Reforming the Education Sector: Egypt as a Case Study - Magued, Shaimaa (The Arab Journal of Administration, 2025)
This paper introduces anticipatory governance as a bottom-up approach for the educational sector’s development in developing countries. Doing so, it contends that, unlike governments’ top-down approaches in decision-making, the New Public Administration School suggests a mission-oriented and open-minded alternative for reconsidering policy-making toward improving service delivery to citizens. Relying on a qualitative research method based on the text analysis of documents addressing Egypt’s e-learning policy during the COVID-19 pandemic, this study asserts that decentralization, the driving principle of anticipatory governance, is the most suitable alternative for overcoming structural and logistical deficiencies in the educational sector. Through the inclusion of stakeholders in designing policy options, the government would be able to foresee potential challenges and prevent their consequences based on the development of participatory and sustainable policies in response to public needs.